Perceived Peer Relationships in Adolescence and Loneliness in Emerging Adulthood and Workplace Contexts - Chiao, Chi; Lin, Kuan-Chen; Chyu, Laura (Frontiers in Psychology, 2022)
Background A common life-course hypothesis is that negative early-life experiences contribute to poor health in later-life. However, little is known about perceived peer relationships during adolescence and the feeling of loneliness in emerging adulthood. This study explores the perception of adolescent peer relationships in a school context and its association with loneliness in adulthood and in workplace contexts. Methods This study used data from a cohort sample of 2,520 adolescents from the Taiwan Youth Project (N = 2,520), consisting of eleven waves of data collected from 2000 to 2017. Major measures included the Loneliness Scale (6-item de Jong Gierveld short scale) and perceived peer relationships (classroom cohesion and perceived popularity among classmates) in middle school. Multivariate multinomial logistic regressions were used to estimate the associations of perceived peer relationships during adolescence and workplace characteristics with loneliness in adulthood. Results Positive perceived peer relationships in adolescence were significantly related to decreased risk of serious social loneliness [Relative risk ratios (RRR) 0.70, 95% CI: 0.58–0.85] and severe social/emotional loneliness (RRR = 0.76, 95% CI: 0.63–0.91) in adulthood. Workplace satisfaction was a protective factor of severe social/emotional loneliness in employed adults. Conclusion Adolescents who perceived peer relationships in middle school as positive were less likely to report social and emotional loneliness during adulthood. Satisfaction in the workplace characteristics was also associated with lower risk of loneliness in adulthood. Theoretical and policy implications are discussed.